The effect of exports and development spending on Indonesia's economic growth - Jumiana Jumiana (Institute of Accounting Research and Novation (IARN), 2023)
The data used in this study is a 10-year time series data between 2003-2012 which is secondary. Data were obtained from various sources, including the Central Bureau of Statistics (BPS), and scientific journals and other literature related to this research topic. The analytical method used in this study is multiple regression analysis which is used to determine the magnitude of the effect of changing one variable on another variable with the help of SPSS 17. From the regression results above the R squared (R2) value is 0.957, this means 95.7% variation changes in economic growth variables can be explained simultaneously by variations in export and development expenditure variables, the remaining 4.3% is determined by other variables or factors outside the model. for export, the results of the study show that the significance value is lower than the significant level (0.000 <0.05) so that Ho is rejected, Ha is accepted, thus exports have a positive and significant effect on economic growth. While development expenditure, the significant value is greater than the significance level (0.251 > 0.05) so that Ho is accepted Ha is rejected thus the results of the study show that the coefficient of development expenditure (x2), is not significant to Indonesia's economic growth.